Adrenal chromaffin cell function in high-altitude deer mice (Peromyscus maniculatus) - Pranckevicius, Nicole (My University, 2017)
The deer mouse (Peromyscus maniculatus) inhabits a broad altitudinal range from sea level to over 4300m, where they experience continuous hypoxia. Typically hypoxia activates the sympathetic nervous system; however this could become maladaptive in high-altitude residents if it is maintained over chronic periods. We hypothesized that high-altitude deer mice might have altered the physiology of adrenaomedullary chromaffin cells (AMC) in the adrenal gland to avoid chronic activation of the sympathetic response. Highland mice had lower plasma adrenaline levels compared to lowland populations of Peromyscus mice, both before and after acclimation to hypobaric hypoxia. This did not correspond to any apparent changes in AMC Ca2+-signalling dynamics. Instead a profound blunting of catecholamine storage was found in highland AMCs that appeared to underlie the reduction in adrenaline release
Keywords: High-altitude adaptation; Nicotinic Acetylcholine Receptors; Calcium Signalling; Catecholamine Storage; Adrenaline